Payer perspectives on pharmacogenomics testing and drug development. (January 2009) - Epstein, Robert S; Frueh, Felix W; Geren, Dawn; Hummer, Doris; McKibbin, Scott; O''Connor, Susan; Randhawa, Gurvaneet; Zelman, Benjamin
A series of questions about hypothetical drugs and pharmacogenomic tests was posed to a panel of representatives from the health plan, government and employer sectors in order to elicit suggestions for input on data or study design considerations important for coverage determination. The panel suggested seven areas for drug developers to strongly consider. These areas were to include comparative information on new tests versus usual care, assess the negative predictive value of new tests, measure and report on cost offsets, balance relative risk improvement with absolute risk, consider the policy implications of the products or tests, report percentage responders in addition to group mean improvements, and to include specific pharmacogenomic information in US FDA approved labels. The panel was generally enthusiastic about the promise of the field to improve drug selection or dosing.